Mechanism of NO binding to soluble guanylyl cyclase: implication for the second NO binding to the heme proximal site - Martin, Emil (2012)
Soluble guanylyl cyclase (sGC), the key enzyme for the formation of second messenger cyclic GMP (cGMP), is an authentic sensor for nitric oxide (NO). Binding of NO to sGC leads to strong activation of the enzyme activity. Multiple molecules and steps of NO binding to sGC have been implicated, but the target of the second NO and the detailed binding mechanism remain controversial. In this study, we used (15)NO and (14)NO and anaerobic sequential mixing-freeze quench EPR to unambiguously confirm that the heme Fe is the target of the second NO. Linear dependence on NO concentrations up to 600 s(−1) for the observed rate of the second step of NO binding not only indicates that the binding site of the second NO is different from that in the first step, i.e. the proximal site of the heme, but also support a concerted mechanism in which the dissociation of the His105 proximal ligand occurs simultaneously with the binding of the second NO molecule. Computer modeling successfully predicts the kinetics of formation of a set of five-coordinate NO complexes with the ligand on either the distal or proximal site and supports a selective release of NO from the distal side of the transient bis-NO sGC complex. Thus, as has been demonstrated with cytochrome c', a five-coordinate NO-sGC containing a proximal NO is formed after the binding of the second NO.